A Little Less Alone: Surviving Sanism in Art Therapy. Issue 2 (2nd April 2020) - Ehlert, Roxie
Abstract: Sanism is the systematic oppression of people who have experiences often labeled as mental illness . The author, a psychiatrically disabled, queer art therapist, describes her direct experiences of stigma and sanism as a past art therapy student and current art therapy educator. The framework of disability justice, a creative and intersectional response to ableism and sanism, resists pathologizing, medical model approaches to disability and engages art as a means of change-making. Art therapy educators can use a disability justice framework to challenge sanism in the classroom and embrace anti-oppressive pedagogy as a means of dismantling oppressive cultural norms in art therapy.